The Influence Of Financial Literacy And Financial Behavior On Welma-Mybca Mutual Fund Investment Decisions - Mirati, R. Elly; Purwaningrum, Endang; Masjono, Ali (Ekonomi & Bisnis, 2024)
Purpose This study aims to examine and analyze the effect of financial literacy and financial behavior on mutual fund investment decisions at Wealth Management (WELMA) MyBCA. Design/methodology/approach The research method used in this research is quantitative research with a purposive sampling approach. The data analysis technique used is multiple linear regression based on the results of the questionnaire using SPSS 26.0. Findings Financial literacy and financial behavior partially or simultaneously have a positive and significant effect on mutual fund investment decisions at WELMA-MyBCA. Research limitations/implications The limitations in this study are that BCA Bank customers use WELMA-MyBCA in conducting investment transactions and are millennial generations domiciled in Java Island. Originality/value This research is expected to be a policy evaluation of the WELMA feature provided by BCA with a view to assessing the prospects and challenges in investing which are factor in encouraging financial literacy and financial behavior for the millennial generation. Keywords: Mutual Fund, Financial Literacy, Financial Behavior, Investment Decisions, WELMA.